2010
DOI: 10.3171/2009.9.jns09196
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for trigeminal neuralgia: the impact of magnetic resonance imaging–detected vascular impingement of the affected nerve

Abstract: Vascular impingement of the affected nerve was seen in the majority of patients with trigeminal neuralgia. Overall pain relief following GKRS was comparable in those with and without evidence of vascular compression on MR imaging. In subgroup analysis of those with MR imaging evidence of vessel impingement of the affected trigeminal nerve, pain relief correlated with a higher dose to the point of contact between the impinging vessel and the trigeminal nerve. Such a finding may point to vascular changes affordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Recently, it has been evidenced that overall pain relief following GKRS was comparable in patients with and without evidence of vascular compression on MRI. In the subgroup analysis of those with MRI evidence of vessel impingement of the affected trigeminal nerve, pain relief correlated with a higher dose to the point of contact between the impinging vessel and the trigeminal nerve 132. Nonetheless, in a recent prospective cohort study comparing GKRS and MVD, the last one was significantly superior to GKRS in maintaining a pain-free status and provided similar early and superior longer-term patient satisfaction rates compared to GKRS 133…”
Section: Advances In Surgical Therapymentioning
confidence: 95%
“…Recently, it has been evidenced that overall pain relief following GKRS was comparable in patients with and without evidence of vascular compression on MRI. In the subgroup analysis of those with MRI evidence of vessel impingement of the affected trigeminal nerve, pain relief correlated with a higher dose to the point of contact between the impinging vessel and the trigeminal nerve 132. Nonetheless, in a recent prospective cohort study comparing GKRS and MVD, the last one was significantly superior to GKRS in maintaining a pain-free status and provided similar early and superior longer-term patient satisfaction rates compared to GKRS 133…”
Section: Advances In Surgical Therapymentioning
confidence: 95%
“…5,23 Furthermore, TN attributed to microvascular compression at the site of the DREZ is by far the most accepted theory in terms of the mechanism of TN based on the findings of Barker et al 1 The disparity in PR duration in this study may indicate that the location of the DREZ is highly variable, and this variability in DREZ location has been described by De Ridder et al 3 Our group previously published a study regarding the impact of vascular compression on the efficacy of radiosurgery for TN. 22 In that study of 106 patients with TN, GKRS proved more effective when the radiosurgery was delivered closer to the point of vascular impingement on the trigeminal nerve. That finding may recapitulate the more favorable pain relief after radiosurgery when targeting the proximal DREZ.…”
Section: Discussionmentioning
confidence: 99%
“…Brisman and Mooij, in a series of 172 patients with trigeminal neuralgia treated with a maximum dose of 75 Gy, demonstrated that treatments in which the brainstem received 20% or more of the maximum dose to a volume of 20 mm 3 provided better pain control than those who had smaller volumes targeted with lower doses [19]. In work from our group, we have observed that a higher dose delivered to the point of contact between an impinging vessel and the affected trigeminal nerve is more likely to induce pain relief in those undergoing radiosurgery for typical trigeminal neuralgia [25]. In cases where higher doses were required, the isocenter was usually placed away from the brainstem, presuming that would decrease the risk of side effects.…”
Section: Target Of Radiosurgery For Trigeminal Neuralgiamentioning
confidence: 77%